Investigating features in augmented visual feedback for virtual reality rehabilitation of upper-extremity function through isometric muscle control - Sanford, Sean; Collins, Brian; Liu, Mingxiao; Dewil, Sophie; Nataraj, Raviraj (Frontiers in Virtual Reality, 2022)
This study investigated how variations in the complexity and intermittency of augmented visual guidance affect the performance of an isometric muscle control task with a computerized platform. This novel platform has been developed to rehabilitate upper-extremity function after neuromuscular dysfunction (e.g., spinal cord injury, stroke) while utilizing: 1) a position-adjustable arm brace for gravity support; 2) a myoelectric command interface; 3) virtual reality (VR) for motor training. This initial investigation evaluates how augmented visual guidance during training affects the motor performance of neurotypical participants during a challenging (i.e., multiple targets) motor task. Previous studies have demonstrated how augmented feedback can accelerate motor learning. Still, how specific feedback features of complexity and intermittency can influence the learning of a challenging, force-driven motor task remains largely unknown. Results from this study elucidate new motor control principles and suggest how augmented guidance may be leveraged in designing VR motor rehabilitation programs, which are highly flexible and customizable to individual users. This study demonstrated that simpler and more intermittent feedback typically resulted in better performance (i.e., shorter computerized motion pathlengths). Supplementary results suggested these feedback modes also reduced cognitive loading (i.e., alpha/beta band magnitudes in electroencephalography) but increased physical arousal (i.e., higher skin conductance). In sum, this study indicates that for complex, force-driven tasks, augmented guidance must be presented selectively to accelerate gains in motor performance. This study suggests simple and intermittent feedback avoids cognitively overwhelming the user while encouraging physical engagement that supports better performance.